Chemical Interaction of Dapsone Absorbed in Polyallylamine. Issue 1 (August 2017) - Gonzalez‐Torres, Maribel; Cruz, Guillermo J.; Gomez, Lidia M.; Gonzalez‐Salgado, Francisco; Basurto, Rafael; Olayo, Maria Guadalupe.
Abstract : A study on the absorption, chemical interaction and release of dapsone (Dp) in iodine doped polyallylamine (PAl/I) is presented in this work. Dp and PAl/I are being studied as implants in the central nervous system with severe injuries to reduce secondary destruction of healthy tissue. The absorption was performed by immersion of Dp in ethanol with a 10:1 (PAl/I:Dp) mass ratio, supported by a previous PAl/I lyophilization. Morphology and chemical structures were studied before and after adding the drug to the polymer in which Dp covered most of the surface. Once in contact, Dp and PAl/I had enough physicochemical interaction to lose their highest oxidized or resonant chemical states with the respective creation of other reduced configurations. Dp release was tested in Krebs‐Ringer solutions obtaining two mechanisms, one rapid in the first 5 min and another much slower after that, which apparently depends on the Dp solution saturation.